Extracellular vesicles in ovarian cancer: applications to tumor biology, immunotherapy and biomarker discovery. (2nd April 2016) - Nawaz, Muhammad; Fatima, Farah; Nazarenko, Irina; Ekström, Karin; Murtaza, Iram; Anees, Mariam; Sultan, Aneesa; Neder, Luciano; Camussi, Giovanni; Valadi, Hadi; Squire, Jeremy A.; Kislinger, Thomas
ABSTRACT: In recent years there has been tremendous interest in both the basic biology and applications of extracellular vesicles (EVs) in translational cancer research. This includes a better understanding of their biogenesis and mechanisms of selective cargo packaging, their precise roles in horizontal communication, and their application as non-invasive biomarkers. The rapid advances in next-generation omics technologies are the driving forces for these discoveries. In this review, the authors focus on recent results of EV research in ovarian cancer. A deeper understanding of ovarian cancer-derived EVs, the types of cargo molecules and their biological roles in cancer growth, metastases and drug resistance, could have significant impact on the discovery of novel biomarkers and innovative therapeutics. Insights into the role of EVs in immune regulation could lead to novel approaches built on EV-based immunotherapy.